SPATIAL VARIABILITY IN THE BELAIT FORMATION: IMPACT ON RESERVOIR CHARACTERIZATION AND MANAGEMENT CONSIDERATIONS (EOR). - Padmanabhan, Eswaran (2010)
Sedimentary facies in the Belait Formation in North-eastern Sarawak show tremendous spatial and temporal variability. This variability needs to be evaluated to increase our understanding and management of reservoirs and thereby assist in enhanced oil recovery endeavors. The heterolithic facies in the north shows varying proportions of sand to clay. The main variations in sandstones in this area include laterally continuous or discontinuous mud-drapes, with varying degrees of thickness, lengths and density per square metre (mud drape facies), close spacing in migrating channels with fills of sand with high carbon contents at high geomorphic positions, presence of remnants of conglomerates (oligomict), and the occurrence of dark gray massive shale facies and massive sandstone facies in top stratigraphic positions. The central section along the North-South ridge comprises has a similar geology in addition to the occurrence of massive sandstone facies and dark gray massive shale facies. Paleocurrent analysis shows that these fluvial sediments were part of a deltaic system with flow directions between 40o and 180o. Temporal analysis indicates that magnitude of the current was fairly consistent. A conglomerate (oligomict) facies overlies the Setap Shale Formation in the South. Variations in fabric are abundant. Thermal conductivity studies suggest that the behavior of these reservoir quality rocks is strongly dependent on fabric. The variability created by the heterogeneity in the Belait Formation has the potential to impact enhanced oil recovery considerations and the efficiency of respective units in the Formation to function as seals or as reservoirs.